Determinants of vaccine uptake in HIV-affected families from West Bengal - Bikas K. Arya; Tila Khan; Ranjan Saurav Das; Rajlakshmi Guha; Sangeeta Das Bhattacharya (Human Vaccines & Immunotherapeutics, 2021)
Children living with Human Immunodeficiency virus (HIV; CLH) have special vaccine needs. Determinants of household-level uptake of vaccines need to be examined in high-risk families with CLH. We previously conducted a study on the impact of Haemophilus influenzae type b conjugate vaccine and pneumococcal conjugate vaccine (PCV-13) in 125 HIV-affected families and 47 HIV-unaffected families in West Bengal. We then interviewed 99 of these 172 families who had participated in the study to understand the household-level factors that determine vaccine uptake. Sixty-four of the 99 families had one or more CLH. Within these 64 families, 30% of CLH had missed vaccines under the universal immunization program (UIP), compared to only 6% of HIV-uninfected children (HUC) (p = .001). Maternal HIV positivity in a family increased risk of missing UIP vaccines nearly five times (4.82, p = .001). Almost all families accessed UIP vaccines at local primary vaccination centers, but 14% of families experienced stigma due to HIV and avoided getting one or more vaccine doses. In contrast, in our study, 100% of HIV-affected families actively sought PCV-13 and HibCV, despite having to travel. Factors that influenced uptake included awareness generation and activation by an outreach worker and availability of vaccines on pick-up days for anti-retroviral therapy. Eighty-six percent of families strongly recommended PCV-13 to other families. To conclude, while we found that CLH have barriers to getting vaccinations, a program designed to take into consideration the obstacles that HIV-affected families face showed a high rate of vaccine uptake.